All-island coordination of energy infrastructure and renewable energy supports - Cathal Menton; Genaro Longoria; Niall Farrell; Muireann Lynch (The Economic and Social Research Institute (ESRI), 2022)
This research project quantifies the impact of renewable energy policy co-ordination in the Single Electricity Market of Ireland. Renewable energy targets are determined independently by both jurisdictions on the island. To date, renewable electricity targets have been similar in each jurisdiction. The primary contribution of this paper is to identify the impact of continued alignment, as compared to a counterfactual where the levels of renewable targets are unaligned. In doing so, the analysis considers whether unaligned policy targets could lead to sub-optimal infrastructure development on the island and calculates any resulting costs, should they exist. The project also considers the principle of 'effort sharing', as outlined in the Kyoto Protocol, by examining a scenario where there is a single target for the whole island of Ireland. A further contribution of this analysis is to consider the proposed North-South 400 kV Interconnection development. We consider the effect this installation may have on the power system, and how it will interact with various configurations of renewable energy policy targets.
Keywords: 330; Stromnetz; Strommarkt; Erneuerbare Energie; Nachhaltige Energieversorgung; Irland